Professionalization of academic teaching in Latin American Universities to address SDGs applying the Stages of Concern Theory - Makrakis, Vassilios; Kostoulas-Makrakis, Nelly; Siegmund, Alexander; Martelletti, Delfina María; Álvarez-Vanegas, Alejandro; Castillo Ceja, Mateo Alfredo; Gonzalez, Miguel; Carrillo Artavia, Carolina; Jiménez-Elizondo, Nadiarid; Velázquez Muñoz, David Eduardo; Jimenez-Elizondo, Alicia; Larios, Nikolaos (Sustainability, 2025)
In the face of escalating sustainability challenges globally, such as climate change, poverty, inequality, and injustices, the need for a systematic approach to tackle them through the infusion of Sustainable Development Goals (SDGs) in higher education has become increasingly critical. This article explores the crucial issue of professionalizing academic teaching, emphasizing the readiness of academic teachers to cope with sustainability and SDGs in higher education. Using the Stages of Concern Theory and the Concerns-Based Adoption Model (CBAM) to professionalize academic teaching to address SDGs in teaching, learning, and the curriculum, a sample of 1566 academic teachers in nine Latin American universities responded to the survey. This study aimed to answer two key questions, as follows: (1) How do the years of teaching experience affect academic staff’s stages of concern? (2) How do different academic teaching areas influence the academic staff’s stages of concern? The trend reveals that faculty members with fewer than four years of service scored higher than those with twenty or more years. Similarly, academic teaching staff from the Education Sciences have a significantly higher mean score and effect size than faculty members from the Humanities, Engineering, Social Sciences, Sciences, and Health Sciences across all stages of concern. However, despite these differences, professional development initiatives should be designed to match all teaching staff regardless of years of service and subject area by encouraging teamwork and increasing understanding of the critical importance of transformative teaching and learning.